2018
DOI: 10.3389/fphar.2018.01252
|View full text |Cite
|
Sign up to set email alerts
|

Selective Blockade of HCN1/HCN2 Channels as a Potential Pharmacological Strategy Against Pain

Abstract: A prominent role of hyperpolarization-activated, cyclic nucleotide-gated (HCN) channels has been suggested based on their expression and (dys)function in dorsal root ganglion (DRG) neurons, being likely involved in peripheral nociception. Using HCN blockers as antinociceptive drugs is prevented by the widespread distribution of these channels. However, tissue-specific expression of HCN isoforms varies significantly, HCN1 and HCN2 being considered as major players in DRG excitability. We characterized the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…As HCN2, HCN3, or mixed HCN2 + HCN3 channels are functionally expressed in GH 3 cells [24], OXAL-induced stimulation of I h in native cells does not tend to be isoform specific, although our experimental results showed that OXAL could modify the amplitude and gating of I h in GH 3 and R1220 cells. Because of the importance of I h (i.e., HCNx-encoded currents) in contributing to excitability and automaticity of electrically excitable cells [18,22,28,38,40,50], findings from the present results could provide novel insights into electrophysiological and pharmacological properties of OXAL or other structurally related compounds [19,20].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As HCN2, HCN3, or mixed HCN2 + HCN3 channels are functionally expressed in GH 3 cells [24], OXAL-induced stimulation of I h in native cells does not tend to be isoform specific, although our experimental results showed that OXAL could modify the amplitude and gating of I h in GH 3 and R1220 cells. Because of the importance of I h (i.e., HCNx-encoded currents) in contributing to excitability and automaticity of electrically excitable cells [18,22,28,38,40,50], findings from the present results could provide novel insights into electrophysiological and pharmacological properties of OXAL or other structurally related compounds [19,20].…”
Section: Discussionmentioning
confidence: 86%
“…For example, OXAL has been demonstrated to suppress different types of voltage-gated K + or Na + currents in various preparations, such as myelinated axons, sciatic-nerve preparations, and motoneuron-like cells [11,[13][14][15][16]. Of interest, this agent was also recently reported to activate I h in isolated dorsal root ganglion neurons, and this action is thought to be implicated in its modifications of pain sensation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also necessary to point out that the potential of HCN blockers in cardiac pathologies and in the management of pain is well established and that the compounds able to increase I h (e.g., oxaliplatin) may have the therapeutic potential [42,43]. Caution thus entails being raised in attributing the action of CIL on either cardiac function or neuronal networks widely to the block of I h [2,18,19,30,[34][35][36]44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the next set of experiments, we examined and compared the effects of croton-03, YS-035, zatebradine, croton-03 plus SQ-22536, and croton-03 plus oxaliplatin on I h amplitude in GH 3 cells. YS-035 or zatebradine was recognized as an inhibitor of I h [19,29], oxaliplatin was recently demonstrated to stimulate I h [30,31], and SQ-22536 is an inhibitor adenylate cyclase. As illustrated in Figure 4, similar to the effect of croton-03 on I h described above, the addition of either YS-053 (3 µM) or zatebradine (3 µM) was effective at depressing I h amplitude.…”
Section: Effect Of Croton-03 Ys-035 Zatebradine Croton-03 Plus Sq-mentioning
confidence: 99%